A Qualitative Study of Intimate Partner Violence From the Perpetrator’s Perspective - Ager, Richard D. (Journal of interpersonal violence, 2021)
Cognitive–behavioral treatment (CBT) has shown promising results in reducing aggression in intimate partner violence (IPV) relationships. A cornerstone of effective CBT is the assessment and measure of cognitions, behaviors, interactions, and conditions surrounding the violence. Unfortunately, there is limited perpetrator-based research that focuses on these aspects of IPV. The purpose of this study was to question perpetrators about the behaviors, interactions, cognitions, and conditions that precipitate and maintain abuse. Such information, along with similar data collected in a companion study of victims, is intended to assist in better understanding perpetrator violence, which can serve as the foundation of effective cognitive–behavioral (CB) IPV assessment, measurement, and treatment. Twelve heterosexual perpetrators receiving treatment for IPV completed structured audiotaped interviews focusing on CB phenomena, that is, the cognitions, behaviors, feelings, interactions, and conditions perpetrators have before, during, and after an IPV incident. Transcripts were coded and analyzed to develop a broad categorized list of discrete IPV phenomena over time. Among the findings relating to violent incidents was indication that despite the progression of abuse that compels perpetrators uncontrollably toward a violent episode, both partners simultaneously engage in numerous preventive attempts. The findings are ultimately intended to contribute to an instrument or treatment assessment method that can more accurately measure IPV phenomena emphasizing core CB concepts.